Alat Ukur Tebal Papan Komposit Berbasis Mikrokontroler - Ferisa Pratiwi; Tetti Novalina Manik; Arfan Eko Fahrudin (Jurnal Fisika FLUX, 2017)
Thickness measurement tools of materials based on microcontroller has been done. This instrument consists of mechanical system, ultrasonic sensor HC-SR04, Arduino UNO microcontroller module, stepper motor, and MicroSD Card module. Ultrasonic sensor HC-SR04 is integrated with the Arduino UNO module and measurement data is displayed on LCD 20 X 4 characters, then the measurement result of date was stored automatically in MicroSD Card. The accuracy of the thickness meter is done by comparing between the measurement data from the thickness meter with the measurement manually. The measurement result of composite board thickness has 93,8% accuracy on flat composite and 50% on the uneven composite board test.